Aplikasi Ekstrak Kompos Meningkatkan Hasil dan Menekan Penyakit Padi Sistem Ratun di Sawah Pasang Surut Kabupaten Banyuasin - Suwandi Suwandi; Muhammad Ammar; Chandra Irsan (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Suwandi et al. 2012. Application of Extract Compost Increased Yield and Suppressed the Diseases of Ratoon Rice Crop in Tidal Swamp of Banyuasin Regency. JLSO 1(2):116-122.A field study was conducted to test the effects of the biofertilizer preparations on yield and diseases of ratoon rice crop in the reclaimed tidal swamp of Telang II, Banyuasin Regency of South Sumatra. The biofertilizer were prepared either as dormant inoculant in liquid formulation or active inoculant in compost extract. Both preparations contain chitinolytic, cellulolytic and phosphate solubilizing bacterial community. The result showed that the yield of ratoon crops of Ciherang rice variety in the suboptimal land increased by 67% (923 kg/Ha) in response to single spraying of the compost extract. The ratoon sprayed with the compost extract had a lower incidence of neck blast and panicle blight and produced less empty grains compared to non-sprayed control. The application of extract compost appears to be a feasible method for increasing production of ratoon rice in tidal swamps.